Psoralen Induced Liver Injury by Attenuating Liver Regenerative Capability - Zhou, Wang; Chen, Xi; Zhao, Guolin; Xu, Dengqiu; Jiang, Zhenzhou; Zhang, Luyong; Wang, Tao (Frontiers in Pharmacology, 2018)
Psoralen is a major component of the common traditional Chinese medicine Fructus Psoraleae (FP). In this study, we focused on psoralen to explore FP-induced hepatotoxicity and the underlying mechanisms. The acute oral median lethal dose of psoralen in ICR mice was determined to be 1673 mg/kg. C57BL/6 mice were administered psoralen intragastrically at doses of 400 mg/kg or 800 mg/kg, and were sacrificed 24 h after treatment. Changes in various hepatotoxicity indicators demonstrated that psoralen can cause mild liver injury in mice. Psoralen inhibited the viability of normal human liver L02 cells in vitro by inducing S-phase arrest. In addition, psoralen in both the mouse livers and L02 cells upregulated cyclin E1 and p27 protein levels. The 2/3 partial hepatectomy mouse model was used to further explore the effects of psoralen on the liver regeneration and hepatocellular cycle arrest in vivo. The results showed that the decrease of liver regenerative and self-healing capabilities induced by hepatocellular cycle arrest may play an important role in the hepatotoxicity of psoralen. The further mechanism researches indicated that psoralen-induced hepatotoxicity was associated with inhibition of mTOR signalling pathway and mitochondrial injury; furthermore, MHY, an mTOR activator, partly alleviated the inhibition of mTOR and S-phase cycle arrest induced by psoralen in L02 cells. In conclusion, in this study we showed for the first time, that psoralen significantly induced liver injury in mice; the decrease of liver regenerative and compensatory capabilities induced by hepatocellular cycle arrest may play an important role in the progression of hepatotoxicity associated with the upregulation of cyclin E1 and p27, as well as the inhibition of mTOR signalling and mitochondrial injury. Our findings may contribute to the reduction of hepatotoxicity risk induced by Fructus Psoraleae.